THE CONTRIBUTION OF UNDERSTANDING ROLE AND EXPECTATION ROLE RELATED TO MIDLE MANAGEMENT PERFORMANCE ACHIEVEMENT BASED ON TEN LEADERSHIP ROLE BY MINTZBERG - Muhammad Hidayat (Jurnal Mirai Management, 2019)
This research is to analyze whether there is a link between understanding role and expectation role related to midle management performance achievement. The method used in this research is descriptive analytic method using quantitative approaches. Analytical tools used by the writer is statistical analysis, this tool function is to examine the different average through paired samples t-test and also using rank Spearman 's correlation analytic. The result of paired samples t-test research analytic is to prove that there is a significant difference between midle management understanding role and expectation role center leader based on ten leadership role written by Mintzberg. The correlation analytic by Rank Spearman 's correlation analysis prove that there is thigh and significant link between understanding role based on ten leadership role written by Mintzberg among branch leader work achievement.